Making Sense of Radicalization (American Journal of Islam and Society, 2015)
The self-proclaimed Islamic State of Iraq and Syria’s (ISIS) burning to deathof Jordanian pilot Moaz al-Kasasba and beheading of twenty-one Egyptiansin Libya are just the latest incidents in a series of escalating acts of violencethat epitomize the seemingly senseless carnage that so often results from thepolitical radicalization of individual Muslims. As the international media zeroesin on such instances, one often struggles to make sense of the perpetrators’true motives. But understanding the circumstances that lead up to such viciousnessis key if governments are to minimize such acts in the future.What motivates an individual to join a terrorist organization? Is it ideology,politics, poverty, or something else? What might be done to de-radicalize anindividual who has joined a terrorist group? The reality is that there is no singlepathway toward radicalization. In a May 2010 report entitled “Why Youth Joinal-Qaeda,”1 U.S. Army Colonel Matt Venhaus suggested that those seeking tojoin jihadist networks can be divided into revenge seekers needing an outletfor their frustration, status seekers needing recognition, identity seekers in needof a group to join, and thrill seekers looking for adventure.2 Clearly the motivesfor terrorism are differentiated and complex, as opposed to uniform and simple.Thus identifying an overarching pattern to understanding how individualsmight become susceptible to terrorist recruiters and what intervention strategiescan be employed to stop it becomes a very difficult task ...